Association Between Mobile Phone Usage in Road Traffic Environment with The Speed Managing Behaviour Among Young and Aged Population - A Survey - A, SWETAA.; MOHANRAJ, KARTHIK GANESH (The journal of contemporary issues in business and government, 2020)
Travel speed is one of the most critical parameters for road safety; the evidence suggests that increased vehicle speed is associated with higher crash risk and injury severity. Both naturalistic and simulator studies have reported that drivers distracted by a mobile phone select a lower driving speed. Mobile phone use while driving is a major cause of driver distraction, affecting driving performance and increasing accident risk. The aim of the study is to analyse the impact of mobile phone usage in road traffic environment on the speed managing behaviour among young and aged population by survey.A questionnaire was created with a set of 12 questions related to mobile phone usage in a road traffic environment . 100 random participants of adults and aged males and females by random sampling method . The participants were asked to fill the questionnaire in an online forum . The results were collected and formatted in Pie charts, Chi- square test was used and statistically analysed using SPSS.90% of them are aware of road safety while driving. Most of the population wear helmets regularly which is about 59%, 15% of the population wear helmets occasionally and 26% do not wear helmets regularly.84% of them responded that they use bluetooth or headphones while driving and 16% of them responded that they won’t use bluetooth or headphones while driving. 70% of them responded that they get distracted using phones while driving. Mobile phone use while driving is a common driving behavior and poses a serious threat to public health. From the current study it shows that mobile phone usage while driving causes greater distraction. Thus we conclude further measures to be taken in control of usage of mobile phone while driving.